Temporal changes in the diversity and abundance of stingless bee nests in an urbanized environment - Konicek, Jonas (2025)
Introduction: Increasing urbanization has endangered many species to an unknown extent. Stingless bees (Apidae: Meliponini) are highly important pollinators of tropical plants. Some species are well adapted to urban areas and use man-made structures to build their nests. In Costa Rica, there are 59 stingless bee species, but no account of their urban richness and abundance has ever been made. Objective: To describe the composition and dynamics of the social bee community on the campus of the University of Costa Rica in San José over a six-year period. Methods: We systematically searched for stingless bee nests (active colonies) in trees, buildings, walls and other man-made infrastructure within a 31-hectare section of the campus in 2016 and 2022. We investigated species-specific nest heights and the host plant species chosen for nesting. Results: In total, 89 nests were identified, consisting of five species of five genera (Lestrimellita, Partamona, Scaptotrigona, Tetragonisca, and Trigona). From 2016 to 2022, the stingless bee abundance increased by 23.5%, but the species composition remained the same. Tree cavities were the most attractive nesting locations, and their use increased within the sampling period. Overall nest survival was >64% for the study period. Conclusion: All bee species utilized a variety of tree species, but strangler figs (Ficus spp., Moraceae) were the most important for nest construction. Nest height depended on the species and architecture. This work provides a framework for future studies on tropical social bee communities in urban areas and offers valuable information on their nesting biology in this habitat.